PENGOLAHAN LIMBAH LAUNDRY MENGGUNAKAN METODE BIOSAND FILTER UNTUK MENDEGRADASI FOSFAT - Sri Widya Astuti, Mersi Suriani Sinaga (Universitas Sumatera Utara, 2015)
Laundry waste dominant comes from clothes softener and detergent which is one of the environmentally inhospitable material (non-biodegraduble) soit has to be processed before dumped into the waste. The basic material that use in this research is waste laundry. The purpose of this research is to decrease phosphate and surfactant content by biosand filter method which using active carbon adsorbent with ratio of mixed waste laundry and nutrition is 100%:0, 75%:25%, and 50%:50% (in % volume) by anaerobic process. The parameter that being analyzed are Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Volatile Suspended Solid (VSS), daily pH also Phosphate and Surfactant before and after being processed anaerobically. pH for this research arranged in range 6,9-7,5. The largest volume in VSS ratio is 63,55%, COD percentage is 53,67%, phosphate percentage is 74,32%, and surfactant is 53,54%. The reduction of phosphate and surfactant value result by the present of contaminate layer (biofilm) in tank so that produce phosphate and surfactant that have been fill quality based on government regulation of the Republic Indonesia No. 82 of 2001.